Video Digital Untuk Arkeologi - Sofwan Noerwidi (Balai Arkeologi Yogyakarta, 2006)
Research documents in the form of audio-visual as a form of research documentation have not received much serious attention until now. Even though these sources are very potential materials for publishing archaeology to the wider community. This paper will specifically discuss audio-visual documents and their output in the form of digital video documentaries of archaeology. At the Balai Arkeologi Yogyakarta, this form of publication is a product whose output is routinely attempted at the end of each research as well as at other important events relating to archaeological resources.